Physical Modeling and Numerical Analysis of Tsunami Inundation in a Coastal City - Prasetyo, Adi; Yasuda, Tomohiro; Miyashita, Takuya; Mori, Nobuhito (Frontiers in Built Environment, 2019)
This study conducted a physical model experiment to investigate inundation processes in a complex coastal city model using the Hybrid Tsunami Open Flume in Ujigawa Open Laboratory (HyTOFU). The physical model was constructed at a 1:250 scale as an idealization of the coastal town of Onagawa. Two tsunami waveforms were used, hydraulic bore and solitary wave, which were produced by a pump-type wave generator and a mechanical piston-type wave generator, respectively, at HyTOFU. Tsunami wave generation similar to the 2011 Tohoku earthquake tsunami in Onagawa was successfully reproduced, and the spatial distribution of the tsunami wave propagation and inundation processes on land was clearly observed. A comparison of experimental and numerical models was performed using two-dimensional (2D) and quasi-three-dimensional (Q3D) models. The 2D and Q3D results agreed well with the experimental results in terms of maximum water surface elevations and arrival times for hydraulic bore conditions. For solitary wave trials, the maximum water surface elevations of the 2D results were underestimated, and the arrival times in the numerical models were slower than those in the experimental results. In this study, as a benchmark for the 2011 Tohoku earthquake tsunami, the dataset of tsunami inundation is provided, which will be useful to validate other numerical tsunami models.